Teaching Teachers about Astronomy - Heeringa, Coggin (Proceedings of the Wisconsin Space Conference, 2011)
Crossroads at Big Creek, in collaboration with the Door Peninsula Astronomical Society, is dedicated to educational outreach in astronomy. We have had our best results by providing teacher education in the form of continuing education classes and workshops.Â 